Pemanfaatan Pekarangan Mendukung Ketahanan Pangan Masyarakat Desa Kali Upa - Ariance Yeane Kastanja; Zeth Patty; Zakarias Dilago (Universitas Teuku Umar, 2019)
This community service activity was carried out in Kali Upa village, Tobelo Tengah sub-district, with the aim of increasing community knowledge and technology in the cultivation of yard plants, so that each family could strengthen food through these activities. The method used in this activity was counseling and continued with discussions with villagers as a process for transferring knowledge. This service is carried out as one of the village programs to improve the ability of the community to manage their yards of land so that the produce can be consumed as an additional source of family income. Optimizing the use of the yard by planting various types of agricultural crops can meet the food needs of the community also increase community income. In addition, food availability is one of the important factors in supporting community food security, because it is one indicator of welfare of life. Kali Upa Village is an area that has a flat topography and belongs to a group of narrow yard - medium yards, so that the use of plots can be done by combining various types of plants, including a combination of fruit plants, vegetable plants, food plants and other local plants which are adjusted with yard area.